Características clínico-epidemiológicas y laboratoriales de pacientes con neumonía adquirida en la comunidad atendidos en el Hospital Regional de Loreto, 2019 - Ushiñahua Coblentz, Jorge Enrique (2023)
Community-acquired pneumonia remains a significant cause of morbidity and mortality, with an incidence that varies by region and increases with age and comorbidities. At the national level, the fatality rate is considerable, especially in areas such as the eastern region and the north coast, in the Loreto region it presents a high incidence and morbidity and mortality due to pneumonia. For this reason, the purpose of this work is to determine the clinical-epidemiological and laboratory conditions of patients with community-acquired pneumonia treated at the regional hospital of Loreto, 2019. The sample was 97 patients treated in the Internal Medicine area of the Regional Hospital de Loreto, between the months of January to December 2019. Concluding that 23.7 % of patients presented fever, 23.7% dry cough, 47.4% cough with expectoration, 5.2% hemoptysis, 80.4% chest pain, 48.5% headache, 13.4% altered consciousness, 5.2% presented heart rate >125 beats per minute and 85.6% presented tachypnea. Regarding the sociodemographic characteristics, a greater number of patients with an age ? 70 years (50.5%) are observed, 47.4% correspond to male patients, 26.8% had a history of alcoholism and 21.6% a history of smoking, the proportion of deceased patients it was 16.5%, the most frequent comorbidity was arterial hypertension (45). Regarding the laboratory characteristics, it was observed that 72.2% of patients presented leukocytosis, 91.8% showed neutrophilia and 89.7% presented lymphopenia.